Analisa Faktor Penyebab Cacat Produksi Pengisian Gas Oksigen : Studi Kasus di PT SAMATOR Gas Kota Batam - Rony Prasetyo (Universitas Putera Batam, 2018)
The focus of this research is to know factors causing production defects in the filling of oxygen gas in the process of filling storage tanks with specification 99.60% - 99.9% pure oxygen at PT. Samator. This study found several dominant factors that affect the quality of oxygen purity that has been set company. Production output samples were taken in november 2017 for 25 working days with replication system in group and sub group.The data feasibility test is expressed by the adequacy test and data uniformity to ensure that data is eligible for further processing. Data analysis on the calculation of process capability shows the value of Cp <1.33 means the ability of the process of filling the storage tank with 99.60% - 99.9% pure oxygen specification shows the ability is still low so that the quality of the product is in doubt.This result raises the suspicion of factors causing potential defect product as the cause of the low ability process, to know the cause of the low ability of process then fishbone diagram accompanied by chi square statistic test to validate the alleged defect of production find 6 dominant factor that is raw material of air and water content) , Employee Kopetensi, Standard operational procedures that have not been raw, machine maintenance, engine setup and temperature.